DESIGN OF CULINARY TOURISM GIS MOBILE APPLICATIONS IN PADANG CITY BASED ON ANDROID - Khairunnisa, Khairunnisa; Anggraini, Siska Dwi; Mutia, Mutia; Nelisa, Nelisa; David, Gebby Avischa (INFOKUM, 2022)
The city of Padang has culinary tourism that is growing very rapidly because there are many places that provide culinary or souvenir centers when visiting the city of Padang with strategic tourist locations. how to get to the culinary tourism locations they are looking for if they don't use private transportation. This research produces an Android-based Culinary Tourism Geography Information System application in Padang City. This application is connected directly to Google Maps by collecting data on the coordinates of the culinary tourism object and the position of the culinary tourism object itself[9]. The purpose of this system was built to provide information on culinary tourism locations in the city of Padang easily, simply.